A qualitative investigation into the leadership characteristics of Korean coaches - Park, J. K.; Leeds, J. L. (International Journal of Coaching Science, 2013)
Leadership continues to be a focus for the academic literature associated with sports coaching. The purpose of this study was to analyse the leadership characteristics of thirty-one successful coaches in Korea. In order to contrast with traditional methods, a qualitative methodology was utilized. Coaches were interviewed about the leadership characteristics they considered necessary for success in competition and training. The interviews were tape recorded and transcribed verbatim, transcripts were analyzed inductively, and emergent themes were identified. Eight general dimensions were identified: attitude and philosophy, expertise, ability to develop athletes, teaching methodology, management of athletes, psychological strategies, experience, and charisma. These results are discussed in terms of desirable coaching leadership characteristics, with recommendations for further research.